(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Here, I use the concepts of the McMahon field theory (2010) [1] to explain physically what the magnetic field is, how it arises, what it is made of and why we observe it. Other papers I have read explain the magnetic field as vectors only, in mathematical terms, not physical terms. Thus, I wanted a physical explanation of the magnetic field. This paper offers a physical explanation of what the magnetic field is, based on McMahon field theory (2010).